If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -12 + -1y = -15 Solving -12 + -1y = -15 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + -1y = -15 + 12 Combine like terms: -12 + 12 = 0 0 + -1y = -15 + 12 -1y = -15 + 12 Combine like terms: -15 + 12 = -3 -1y = -3 Divide each side by '-1'. y = 3 Simplifying y = 3
| 7x-3x+x-4+5x= | | (6x^5w^2-2xw^6)-(2xw^2)= | | 5b-5-7b-3= | | 4x+24=9x+26 | | -6y-15-7y=-20 | | -6y-15=-20 | | 9t^2+9t-10=0 | | t-46=-30 | | -6y-12+5=-15 | | 9x+3x=y | | 2/5x-6=-16 | | A=(4x+7)(2x+2) | | A=(4x+7)(2x-2) | | y^2+15y-3=0 | | 5y+x+32=5x+y | | A=(4x+7)(2x*2) | | x+-2x=-2 | | 21x^5y-7x^4y^2= | | 12(v+2)-3v=3(3v+1)-8 | | 10x-1=3(3x+2)-5 | | 5x^3-7x^2+8x-7=0 | | A=(9x+5)(4x-7) | | 10y^5+5y= | | 4v+44=7v+5 | | 50-3=8x | | [4x+12]=16 | | -6m^2+8n^2-10n= | | 2x^2-54x=116 | | 2(3t-5)=t+5 | | X+2x+11+x=163 | | 5y-2=17y+34 | | y=3.5x+6 |